ANALISIS QOWA’ID FI’IL MADHI DAN FI‘L MUDHORI’ DALAM SURAH ABASA AYAT 1-10 (Kaidah tafsir fi’i madhi dan mudhori) - Raihannur, Muhammad; Aulia, Eva; Dasuki, Akhmad (Journal Education and Government Wiyata, 2025)
This study aims to analyze the use of the madhi verb and mudhari verb in Surah Abasa verses 1-10. The problem raised is how the use of two forms of verbs in Surah Abasa verses 1-10 and how these verb forms show the messages and ethical values ​​contained in the verse. The method used in this study is a qualitative research method with a type of research included in the category of library research. Data were analyzed based on the grammatical structure of the verb and its relationship to the context of the revelation of the verse (asbab al-nuzul). The results of this study indicate that the madhi verb is used to describe events that have occurred as a form of reprimand and correction of inappropriate preaching approaches, while the mudhari verb is used to emphasize the possibility of similar attitudes occurring again in the future. So that it functions as a warning and the next lesson. From the results of the analysis, the choice of verb forms in these verses turns out to have a deep meaning. Not just a linguistic structure, but implies an important message about manners, social sensitivity and priorities in preaching. This shows that the structure of the madhi and mudhori verbs in verses 1-10 can open up a new understanding of the message of the Qur'an.